Forensic DNA databases - Corte-Real, Francisco (2004)
Genetic databases have been created in several countries: the United Kingdom was the first European country to have, in 1995, a DNA database. Subsequently, the Netherlands and Austria (1997), Germany (1998), Finland and Norway (1999) and many others have introduced or are preparing databases.